2020
DOI: 10.1007/s00018-020-03455-5
|View full text |Cite
|
Sign up to set email alerts
|

PEBP1/RKIP behavior: a mirror of actin-membrane organization

Abstract: Phosphatidylethanolamine binding protein 1 (PEBP1), a small 21kDa protein, is implicated in several key processes of the living cell. The deregulation of PEBP1, especially its downregulation, leads to major diseases such as cancer and Alzheimer's disease. PEBP1 was found to interact with numerous proteins, especially kinases and GTPases, generally inhibiting their activity. To understand the basic functionality of this amazing small protein, we have considered several known processes it modulates and we have d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 108 publications
2
21
0
Order By: Relevance
“…In a previous study on pork Longissimus muscle, we found negative correlations between PEBP1 and L* and a* values (Kwasiborski et al 2008). The role of PEBP1 in determining beef colour may also be related to its interactions with many multifunctional proteins and involvement in the coordination of cytoskeleton changes and energy metabolism (Schoentgen & Jonic 2020). This is also consistent with the observed relationship between PEPB1 and energy metabolism (Figure 3A,B).…”
Section: Capn1 and Pebp1 As Protein Biomarkers Of Beef Coloursupporting
confidence: 90%
“…In a previous study on pork Longissimus muscle, we found negative correlations between PEBP1 and L* and a* values (Kwasiborski et al 2008). The role of PEBP1 in determining beef colour may also be related to its interactions with many multifunctional proteins and involvement in the coordination of cytoskeleton changes and energy metabolism (Schoentgen & Jonic 2020). This is also consistent with the observed relationship between PEPB1 and energy metabolism (Figure 3A,B).…”
Section: Capn1 and Pebp1 As Protein Biomarkers Of Beef Coloursupporting
confidence: 90%
“…In this sense, and despite the described role for RKIP in the regulation of the MAPK/ERK pathway, RKIP has been implicated on the invasive behavior of malignant melanoma cells but not on their proliferative capability [14]. Moreover, Schoentgen and Jonic [16] described the involvement of RKIP on the cortical actin organization during the membrane changes that happen during tumor cell migration. In agreement with previous studies, we confirmed the implication of RKIP on the motility of malignant melanoma cells as RKIP expression was inversely correlated with the migration capability of both, primary and metastatic melanoma cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant transformation of cells implies the acquisition of particular characteristics in terms of survival and proliferative capability, while metastatic spreading depends on enhanced migration and invasion [16]. In addition, tumor persistence seems to rely on a particular subset of cells with acquired "stem cell-like" properties [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Phosphatidylethanolamine-binding protein 1 (PEBP1), which is also referred to as Raf1 kinase inhibitory protein (RKIP), has been found to be potentially involved in diverse biological functions through the regulation of various protein kinases in several signaling pathways, such as the RAF/MEK/mitogen-activated protein kinase (MAPK)/extracellular regulated kinase (ERK), nuclear factor (NF)-κB and PI3K/Akt/mammalian target of rapamycin (mTOR) pathways (25,26). In addition, the influence of PEBP1 on cell apoptosis, proliferation, migration and autophagy has been demonstrated.…”
Section: Introductionmentioning
confidence: 99%